Allelopathic Potential of Subfractions from Aqueous Extract of Spirulina Platensis and Denatured C-phycocyanin - Patchanee Charoenying; Chamroon Laosinwattana; Nawasit Chotsaeng (Current Applied Science and Technology, 2021)
In this laboratory bioassay, crude aqueous extract of Spirulina platensis (Nordst) Geitl. was extracted with 90% aqueous ethanol and 80% aqueous ethanol to achieve three subfractions, green powder (F1), pale-green powder (F2) and deep-blue powder (F3). Each of these subfractions was evaluated for allelopathic activity on Chinese amaranth (Amaranthus tricolor L.) and barnyardgrass (Echinochloa crus-galli (L.) Beauv.). The plant seeds were germinated in vials with three subfractions (250-2000 mg/l concentrations) and distilled water was used as a negative control. The results indicated that subfraction F3 had the highest inhibitory effect on both of the tested plants. All subfractions had an absorbance ratio (A620/A280) lower than the original aqueous extract, suggesting that a denaturation event of the C-phycocyanin (C-PC) component had occurred during the extraction process. After heating a commercial C-PC solution at 90oC for 3 h, the absorbance ratio changed to 0.46, and likewise allelopathic assay revealed that the decolorized C-PC solution retained its allelopathic potential on the tested plants. To confirm these findings, S. platensis powder was extracted with distilled water at 90oC for 3 h and tested for its allelopathic potential using standard Petri dish assay at concentrations of 0.625-5%. The results showed that the hot aqueous extract had an absorbance ratio of 0.38, and its allelopathic activities were similar to those of the aqueous extract. Furthermore, it was found that although C-PC in aqueous extractions denatured, it still retained its allelopathic potential on the tested plants.
Keywords: Allelopathy and phytotoxic interactions; Plant Parasitism and Resistance; Plant responses to elevated CO2